PENEGAKAN DAN PENGUJIAN PERATURAN PERUNDANG-UNDANGAN UNTUK MENINGKATKAN KUALITAS PERATURAN PERUNDANG-UNDANGAN DI INDONESIA - Nunuk Sulisrudatin (JURNAL MITRA MANAJEMEN, 2014)
ABSTRAK The establishment of good legislation is influenced by several factors, the examples the principle of formation of Foundation and legislation, the preparation ofnational legislation, the preparation of program text academic research studiesthrough a deep. Additionally affected by synchronisation and harmonisation oflegislation. If these factors considered, the resulting legislation will be in accordancewith the wishes of the community, so that the public do not feel oppressed and not tofile a lawsuit to the Supreme Court and the Constitutional Court. All these factorshave direct in Act No. 12 year 2011 about the formation of legislation.